Peningkatan Tanggung Jawab Belajar Matematika Melalui Strategi Discovery Learning Pada Siswa Kelas VII Semester Genap MTS Negeri Surakarta II Tahun 2014/2015 - SEPTIANA, Dewi; , Prof. Dr. Sutama, M.Pd (2015)
This study aimed to describe the increased responsibility for students learning math class VIIC MTs Negeri Surakarta II with learning strategy discovery learning. This study uses a classroom action research. Source data comes from teachers and students. Implementation of a class action carried out during two cycles consisting of 4 meetings. Methods of data collection is done through tests, observations, field notes, interviews and documentation. Data analysis techniques used by qualitative descriptive through three stages of data reduction, exposure data, and inference. Validity of data with triangulation of methods and sources. Results of the study, the first application of learning strategy discovery learning can improve students' mathematics learning responsibility MTs Surakarta VIIC class II. Both the increase in the responsibility of learning mathematics, namely 1) the student is able to carry out and complete the task in earnest from the initial conditions (40.00%), in the first cycle (55.00%), and the second cycle (77.50%), 2) the student is able to fulfill the promise of the initial conditions (27.50%), in the first cycle (57.50%), and the second cycle (70.00%), 3) students who want to accept the consequences of his actions from the initial conditions ( 32.50%), in the first cycle (47.50%), and the second cycle (72.50%). Based on the description above concluded that learning with application discovery learning strategies can increase the responsibility of learning mathematics. Keywords: discovery learning, learn math, responsibility